Conocimientos y Prácticas de los antibióticos en los estudiantes de quinto a décimo semestre de la Universidad Antonio Nariño en el año 2020 - 2021. (2021)
The objective of this research is to establish the level of knowledge, attitude and practice bout the use of antibiotics at Antonio Nariño University Dentist students. Methods: The knowledge and practice level were evaluated by an online questionnaire. 308 students from 5 to 10 semesters, from 9 UAN campus. Results: The Knowledge level average reached by students was 82% (Medium); which increases in relation to the semester (p = 0.004). Senior students (85%) obtained a higher level of knowledge than Juniors (80%). (p = 0.00002). The level of knowledge is a dependent variable of the level (p = 0.00045). Regarding The Practice evaluation, the general result of the University is 78% (Medium). Senior students scored 85%, which is higher than Junior students (80%). (p = 0.003). 96% of students most frequently prescribe Amoxicillin as the first choice. The diagnosis with the highest prescription by the students was acute apical abscess (86%).